Proton beam radiotherapy as part of comprehensive regional nodal irradiation for locally advanced breast cancer. Issue 2 (May 2017) - Verma, Vivek; Iftekaruddin, Zaid; Badar, Nida; Hartsell, William; Han-Chih Chang, John; Gondi, Vinai; Pankuch, Mark; Gao, Ming; Schmidt, Stacey; Kaplan, Darren; McGee, Lisa
Abstract: Purpose: This study evaluates acute toxicity outcomes in breast cancer patients treated with adjuvant proton beam therapy (PBT). Methods: From 2011 to 2016, 91 patients (93 cancers) were treated with adjuvant PBT targeting the intact breast/chest wall and comprehensive regional nodes including the axilla, supraclavicular fossa, and internal mammary lymph nodes. Toxicity was recorded weekly during treatment, one month following treatment, and then every 6 months according to the Common Terminology Criteria for Adverse Events (CTCAE) v4.0. Charts were retrospectively reviewed to verify toxicities, patient parameters, disease and treatment characteristics, and disease-related outcomes. Results: Median follow-up was 15.5 months. Median PBT dose was 50.4 Gray relative biological effectiveness (GyRBE), with subsequent boost as clinically indicated ( N = 61, median 10 GyRBE). Chemotherapy, when administered, was given adjuvantly ( N = 42) or neoadjuvantly ( N = 46). Grades 1, 2, and 3 dermatitis occurred in 23%, 72%, and 5%, respectively. Eight percent required treatment breaks owing to dermatitis. Median time to resolution of dermatitis was 32 days. Grades 1, 2, and 3 esophagitis developed in 31%, 33%, and 0%, respectively. Conclusions: PBT displays acceptable toxicity in the setting of comprehensive regional nodal irradiation.